Electrochemical properties of graphene - Tee, Keat Kee (2016)
Nano-carbon materials have become of great interest as the central issue of nanotechnology in chemistry, and electronic device applications right after the discovery of fullerenes and carbon nanotubes. Graphene, which is known as a single sheet of graphite, is categorized as nano carbon-based materials. Within these materials, the p-orbitals are confined in a unique geometrical structure, built using benzene hexagonal rings as basic blocks, this unique geometrical structure has an important role in contributing to a large variety of electronic structures. Also, carbon nanotube’s electronic structures vary from a semiconductor to metal based on factors like their chirality and diameter. Graphene is a two-dimensional material with a bonded lattice of sp2 carbon atoms. Graphene forms the basic building block of carbon nanomaterials, such as one-dimensional carbon nanotubes as well as zero-dimensional fullerenes. As Graphene displays unique structural geometry and useful physical properties, it has a great potential in applied electronics. Application of Graphene includes transistors, electrodes, and also other electronic devices. In this project, carbon and nickel are first sputtered onto the substrate. Graphene was fabricated using rapid thermal processing which was right after sputtering. The thickness of carbon and nickel are controlled using the duration of individual sputtering with the aid of a timer on the sputtering machine. Thereafter, the Graphene layers were characterized using Raman spectroscopy and analyzed using 4 point probe and electrochemical testing.